Analysis of work life balance, job satisfaction and its effect on the performance of employees of the General Bureau of the Regional Secretariat of the Riau Islands Province - Ngaliman, Ngaliman; Catrayasa, I Wayan; Khairil, Khairil (Studi Ekonomi dan Kebijakan Publik, 2025)
Purpose: This study analyzes the influence of work-life balance, work environment, and workload on performance through job satisfaction as a mediating variable on employees of the General Bureau of the Regional Secretariat of the Riau Islands Province. Methodology/approach: A quantitative method was used with SEM-PLS analysis on data collected from 120 employees of the General Bureau, Riau Islands Provincial Secretariat. Results: Using primary data from 120 employees, this study found that work-life balance and workload have a significant influence on performance through the results of the path coefficient, meaning that the job satisfaction variable can mediate the influence of endogenous variables of work-life balance and workload on the performance variable. This can be explained by the fact that with the mediation of job satisfaction, when there is an increase in work-life balance and workload, employee performance will increase. Conclusions: Improving job satisfaction enhances performance, especially when managing workload and work-life balance. Limitations: The study is limited to one public institution and excludes factors such as leadership and compensation. Contribution: This study highlights the importance of job satisfaction as a mediator to improve employee performance in the public sector.